Effects of angiotensin converting enzyme inhibitors and angiotensin II receptor antagonists on mortality and renal outcomes in diabetic nephropathy: systematic review. Issue 7470 (30th September 2004) - Strippoli, Giovanni F M; Craig, Maria; Deeks, Jonathan J; Schena, Francesco Paolo; Craig, Jonathan C
Abstract: Objective To evaluate the effects of angiotensin converting enzyme (ACE) inhibitors and angiotensin II receptor antagonists (AIIRAs) on renal outcomes and all cause mortality in patients with diabetic nephropathy. Data sources Medline, Embase, the Cochrane controlled trials register, conference proceedings, and contact with investigators. Study selection Trials comparing ACE inhibitors or AIIRAs with placebo or with each other in patients with diabetic nephropathy. Data extraction Mortality, renal outcomes (end stage renal disease, doubling of serum creatinine concentration, prevention of progression of microalbuminuria to macroalbuminuria, remission of microalbuminuria), and quality of trials. Data synthesis 36 of 43 identified trials compared ACE inhibitors with placebo (4008 patients), four compared AIIRAs with placebo (3331 patients), and three compared ACE inhibitors with AIIRAs (206 patients). We obtained unpublished data for 11 trials. ACE inhibitors significantly reduced all cause mortality (relative risk 0.79, 95% confidence interval 0.63 to 0.99) compared with placebo but AIIRAs did not (0.99, 0.85 to 1.17), although baseline mortality was similar in the trials. Both agents had similar effects on renal outcomes. Reliable estimates of the unconfounded relative effects of ACE inhibitors compared with AIIRAs could not be obtained owing to small sample sizes. Conclusion Although the survival benefits of ACE inhibitors for patients with diabetic nephropathy are known, the relative effects of ACE inhibitors and AIIRAs on survival are unknown owing to the lack of adequate head to head trials.